Early Childhood Education in Ireland: Change and Challenge - Rosaleen MURPHY (International Electronic Journal of Elementary Education, 2015)
Early childhood care and education in Ireland has come under increasing scrutiny in recent years, as a result of public concern about standards in some early years services. Services for children before they enter primary school are largely the responsibility of the department of health, while children in the formal school system are the responsibility of the department of education. This split is reflected in the pay, working conditions and qualifications of those working in each sector. Primary education is state funded; pre-school care and education has been seen as the responsibility of parents, and is among the most expensive in Europe. Investment in early years services is low and has been focused on expanding the number of places. There is now more co-ordination at government level and improved standards and frameworks for quality in early education (Síolta) and for early learning (Aistear) have been put in place. However, expanding services without paying equal attention to quality will not bring the desired benefits either to individual children or to society. Regulation and enforcement are important but are only one element of quality, and more attention needs to be paid to developing the early years workforce and improving their working conditions.